COVID-19 di ERA 4.0, Disrubsi dalam Disrubsi: Bertahan di Tengah Pandemi Antara Gangguan dan Inovasi - Mohamad Arif Majid (ASANKA: Journal of Social Science And Education, 2021)
The world has started the industrial revolution era or 4.0 era since 1995 in which the industrial world integrated cyber and automatic technology. This resulted in massive changes through technology which later reduce boundaries among physical, digital, and biological world. The main character of 4.0 era is disruption on which out-of-date companies, products, or models are disrupted by the fierce competition. The disruption impacts on many fields, including Islamic education world. The world problems are exacerbated with the coming of Corona virus in China at the end of 2019 and then it spreads to many countries and becomes global pandemic. Thus, it is a disruption within disruptions when a new complex problem comes before previous problems have not been overcome. This paper discusses about this issue and comprehensive solutions to this hard situation will be explained further